Understanding the Lives of Children in Institutional Care and its Effects on Development - Rajesh, Anubha; Naaz, Seema; Shujat, Aghna (Voices of Teachers and Teacher Educators, 2022)
The detrimental effects of growing up in institutional care are pronounced due to structural adversities faced by children. Research confirms that Child Care Institutions (CCIs) mar children’s socio-emotional, cognitive development and acquisition of formative academic skills. An intervention research was undertaken for ensuring holistic development of children in a Delhi based CCI. The present paper is a part of the larger intervention research. This paper aims to provide an insight into the lives of children residing in CCI along with perceptions of significant stakeholders regarding academic challenges faced by institutionalized children. The paper further attempts to examine the effect of developmentally appropriate pedagogical interventions for children in institutions through a pre and post test approach. A sample of 14 children aged 5-10 years were purposively selected as a part of this research. Informal discussions using unstructured interview guides were conducted with 9 stakeholders to understand the concerns and issues related to academic problems encountered by children. The performance gains from pre to post assessment also inform the effectiveness of the holistic approach when compared to a compartmentalized focus on academic performance. The findings are indicative of need for strengthening existing CCIs by providing training and supportive supervision to stakeholders to ensure quality care for children.